Development and Validation a new method for determination Iron (III) in soil sample of ishaqi irrigation project using Dispersive Liquid-Liquid Microextraction - Younis, Hawraa Rahman; Nsaif, Ayat Abd-Aljaleel; Sabir, Noor-Alhuda A.; AL-Dulaimy, Marwa A.Abdullah (Iraqi Journal of Science, 2026)
In this work, simple and rapid dispersive liquid-liquid microextraction procedure was developed for determination Fe (III) levels in soil sample. The detection was carried out by using Shimazu uv-visible spectrophotometer at wavelength of 620 nm. The developed method relies on a complexation reaction between Fe (III) with methylthymol blue (MTB) in an acetate buffer at pH= 5, conducted at a temperature of 25 0C. Subsequently, a mixture of methylene chloride (for extraction) and acetonitrile (for dispersive) was then quickly injected in solution. After microextraction, the organic and aqueous phases were separated by centrifugation and the resulting blue-colored complex was measured at 620 nm. The parameters governing for extraction efficiency and complex formation were systematically identified and optimized for maximum effectiveness. Optimal experimental conditions yielded linear responses for Fe (III) concentrations between 2 and 50 μg/mL, as predicted. The results showed an intra-day variability of 0.114% and an inter-day variability of 0.698% for five measurements using a concentration of 40 μg/mL. Finally, the developed method was successfully applied for the determination of Fe (III) in different soil samples.